(untitled) (Brazilian Journal of Health Research, 2022)
Introduction: Violence against children and adolescents generates different impacts on the lives of victims and aggressors, constituting an important risk factor for mental health problems, thus requiring strategies to develop care for victims in this context. Objectives: To know the strategies adopted by the professionals of a Center for Psychosocial Child and Adolescent Care in the care of children and adolescents who are victims of violence. Methods: Descriptive-exploratory research with qualitative approach, carried out in a Center for Psychosocial Child and Adolescent Care, located in the southern state of Rio Grande do Sul, Brazil. Ten professionals from the multidisciplinary team participated, using the semi structured interview between May and June 2017. The data were interpreted based on the thematic analysis. Results: Professionals presented care strategies such as’ investigating ‘the victims’ reality, identifying disorders possibly triggered by violence, notifying protection agencies, creating a bond with the child and family, psychotherapeutic groups and the ‘play’. Conclusion: The research reveals strategies that intensify the quality of care provided, considering the perspective of protection, but also the rehabilitation and re-socialization of victims, as well as the promotion of a humanized assistance based on the bond between children / adolescents and their families, guaranteeing the completeness of care.